Primary versus secondary stereotypic movements - Fernandez Alvarez, E (Revista de neurologiá, 2004)
Stereotypic movements are repetitive patterns of movements whose physiopathology and relations to other neurobehavioural disorders are still only poorly understood. In this paper our aim is to distinguish between primary stereotypic movements, which are the sole manifestation of an anomaly, while the complementary examinations, except for those involving molecular genetics, are normal; associated stereotypic movements, when they meet primary disorder criteria but there are other coexisting independent neurological signs, that is to say, they are neither the cause nor the consequence of the movement disorder; and secondary stereotypic movements, when they are the consequence of a lesion or acquired neurological dysfunction. Examples of primary stereotypic movements include episodes of parasomnia, such as head rocking, in subjects who are otherwise normal, and stereotypic movements due to emotional disorders, severe environmental deprivation or in institutionalised infants. Examples of associated stereotypic movements are those observed in Rett syndrome, in subjects with sensory defects or with mental retardation due to a variety of causes. And as instances of secondary stereotypic movements we have those that can be seen in infinite like syndrome caused by congenital cerebellar lesions. The purpose of the classification is to lay the foundations for the identification of new syndromes, which would without a doubt facilitate research into their physiopathology, their aetiology and the possible therapeutic attitude to be adopted.